2008
DOI: 10.1177/0256090920080403
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Forex and Stock Markets in India: An Entropy Approach

Abstract: Interactions between the foreign exchange market and the stock market of a country are considered to be an important internal force of the markets in a financially liberalized environment. If causal relationship from a market to the other is not detected, then informational efficiency exists in the other whereas existence of causality implies that hedging of exposure to one market by taking position in the other market will be effective. The temporal relationship between the forex market and the stock market o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
(9 reference statements)
0
16
0
Order By: Relevance
“…Transfer Entropy is also model-independent and is sensitive to non-linear underlying dynamics, unlike, for example, Granger causality [7], to which Transfer Entropy is reduced for auto-regressive processes [8]. Transfer Entropy has been applied to the theory of cellular automata, to the study of the human brain, to the social media, to statistics, and to financial markets [9][10][11][12][13][14][15][16][17][18][19][20] and [2].…”
Section: Introductionmentioning
confidence: 99%
“…Transfer Entropy is also model-independent and is sensitive to non-linear underlying dynamics, unlike, for example, Granger causality [7], to which Transfer Entropy is reduced for auto-regressive processes [8]. Transfer Entropy has been applied to the theory of cellular automata, to the study of the human brain, to the social media, to statistics, and to financial markets [9][10][11][12][13][14][15][16][17][18][19][20] and [2].…”
Section: Introductionmentioning
confidence: 99%
“…They have concluded that FII and Stock Index are positive correlation, but fail to predict the future value. Reddy and Sebastin (2008) make an attempt to study the interaction between the stock price and the foreign exchange markets in India by using daily data on Nifty and the exchange rate of Indian Rupee vis-a-vis US dollar during the period from November 1995 to March 2007. Using various methods like cross-correlation and error correction model, they identify a linear relationship among the variables.…”
Section: Studies In the Indian Contextmentioning
confidence: 99%
“…The major findings of their study include that there is no Granger causality between the exchange rate fluctuation and stock return. Reddy and Sebastin (2008) make an attempt to study the interaction between the stock price and the foreign exchange markets in India by using daily data on Nifty and the exchange rate from November 1995 to March 2007. The result reveals that there exist a low level of interaction between the stock prices and the forex markets of India.…”
Section: Literature Reviewmentioning
confidence: 99%